Compassion satisfaction, burnout and secondary traumatic stress among termination of pregnancy providers in two South African provinces. Issue 7 (23rd May 2018) - Teffo, Mantshi E.; Levin, Jonathan; Rispel, Laetitia C.
Abstract: Focusing on compassion satisfaction, burnout and secondary traumatic stress (STS) among termination of pregnancy (TOP) providers, a cross ‐ sectional study was conducted among these providers in Gauteng and North West provinces of South Africa during 2014 and 2015. During 2014 and 2015, a cross‐sectional study was conducted among TOP service providers in Gauteng and North West provinces. Consented providers completed a self‐administered professional quality of life (PRoQOL) questionnaire, sociodemographic information and possible reasons for working as TOP providers. STATA 13 was used for data analysis. We recruited 105 TOP providers, obtaining 98% response rate. Participants mean age was 43.4 (standard deviation [SD] = 8.7), majority were nurses (70.9%), female (82%), married (47.6%) and 63% were working in hospitals. The overall mean score for compassion satisfaction was high at 42 (SD 5.5). Predictors of compassion satisfaction were finding work stimulating, belief in making a difference, enjoying relationships with other nurses and years of TOP service ( P < 0.05). Province and gender were significant, with significant interaction. Burnout mean scores were average at 33 (SD = 4.0), with belief in helping women to make informed choices a marginally significant predictor of burnout. The overall STS mean score was average with a mean of 23 (SD = 6.8). Significant predictors of STS scores were finding work stimulating, belief in women's rights, belief in allowing informed choices, age and gender. Health policy makers and managers should endeavor to provide employee assistance programs that enhance compassion satisfaction and reduce burnout and STS among TOP providers.